New Bioengineering Strategies Based on Tissue-Specific Extracellular Matrices to Improve Human Endometrial Organoid Models - Frances-Herrero, Emilio; Juarez-Barber , Elena; Ferrero, Hortensia; Cervello, Irene (New Horizons in Medicine and Medical Research Vol. 11, 2022)
Organoids are multicellular, three-dimensional (3D) tissue models that resemble there In vivo tissue. The recent production of 3D structures from primary endometrial cells is driving new investigations of this crucial tissue utilizing precise pre-clinical models for human uterine endometrium. To improve on these 3D models, we sought to evaluate ECM hydrogels derived from decellularized pig endometrium (EndoECM) in preparing and improving current human endometrial organoid culture systems. To accomplish so, we created three lines of human endometrial organoids and cultivated them in optimal and suboptimal culture expansion conditions with or without soluble supplement EndoECM (0.1 mg/mL). The epithelial origin, long-term chromosomal stability, and stemness features of the resulting organoids were all confirmed. Finally, we used proliferation rates and immunohistochemistry approaches to estimate their proliferation potential under various culture conditions. The relevance of a bioactive environment for the maintenance and growth of human endometrial organoids is demonstrated by our findings.